Circadian rhythm in restless legs syndrome - Tang, Mingyang; Sun, Qingqing; Zhang, Yanan; Li, Huimin; Wang, Dong; Wang, Ying; Wang, Zan (Frontiers in Neurology, 2023)
Restless legs syndrome (RLS) is a sensorimotor disorder with a obvious circadian rhythm, as its symptoms often occur or worsen only in the evening or at night. The mechanisms behind the rhythms of RLS have not yet been fully elucidated. This review explores possible causes for the circadian fluctuations of the symptomatology, including the levels of iron, dopamine, melatonin, melanocortin, and thyroid-stimulating hormone in the brain, as well as conditions such as peripheral hypoxia and microvascular function disorders. The metabolic disturbances of the substances above can create a pathological imbalance, which is further aggravated by physiological fluctuations of circadian rhythms, and results in the worsening of RLS symptoms at night. The review concludes with the suggestions for RLS treatment and research directions in the future.